Perspectives on Hypercriminalization and Its Impact on Racially Minoritized Youth: Insights from Juvenile and Human Services Practitioners (Journal of Applied Juvenile Justice Services, 2025)
The criminalization of racially minoritized youth is often examined in the literature on racial and ethnic disparities (RED) and the school-to-prison pipeline. Most of the research in this area focuses on the impact of formalized criminalization on the offending trajectories of racially minoritized youth, often overlooking informal experiences with criminalization and their influence on how these youth construct their self-perceptions. The current study assesses human and juvenile justice service providers’ perceptions of the impact of repeated criminalization on racially minoritized youths’ self-concept and other outcomes. The results of thematic coding showed that practitioners perceived that the ubiquitous experience of regular criminalization altered racially minoritized youths’ self-concept and contributed to other problems, including compounded criminalization, and the development of internalizing and at-risk behaviors. The results suggest that the criminalization process extends beyond juvenile justice processing and access to conventional opportunities.